Information System Strategic Planning To Improve UINSU Medan Service Performance - Ridwan, M; Siregar, Saparuddin (Politeknik Ganesha Medan, 2024)
Facing increasingly rapid technological developments, UINSU Medan's efforts must be supported by developing existing information systems to meet the needs of the community and community. Currently, even though it has implemented an Information System in its activities, UINSU Medan does not yet have an Information System plan for the next 5 (five) years (2023-2027). It is hoped that this SI strategic planning will be able to improve the performance of UINSU services related to the Tri Dharma of Higher Education. The method used in this research is a qualitative survey. Data collection was carried out by observation, interviews, and literature review. The research informants are the managers of the UINSU Information Technology and Database Center (PUSTIPADA), and employees involved in the Information Systems section as well as service users such as students and lecturers. The stages of this research use Anita Cassidy's approach which consists of the visioning phase, analysis phase, direction phase, and recommendation phase. The data obtained was then analyzed using Value Chain analysis, SWOT, Porte's Five Forces, and other supports which were then confirmed by Focus Group Discussion with competent parties. This research recommends an Information Systems roadmap for UINSU Medan consisting of 34 integrated applications to be developed within 5 (five) years from 2023-2027.